Analisis Kinerja Pelayanan Administrasi di Kelurahan Sei Putih Tengah Kecamatan Medan Petisah Kota Medan - Nethasya Tri Ananda Sianturi; Muhammad Husni Thamrin (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Public service is any form of service or service provided by a government or public institution to the public in general. Administrative services are intended to facilitate the needs of citizens in administrative matters such as identity cards, business permits and other administrative services. This study aims to analyze the performance of administrative services in Kantor Lurah Sei Putih Tengah and to observe any obstacles that are inhibiting the functional performance in this Lurah Office. It shows that there are still obstacles in the performance in the administrative service in Kantor Lurah Sei Putih Tengah. The research method used is a descriptive method with a qualitative approach aimed at understanding in depth how and why a phenomenon occurs, as well as to dig the meaning contained in it from the point of view of the subject being studied. Data collection is done with interviews, observations, and documentation techniques. The results of the study show that the officers of the Kantor Lurah Sei Putih Tengah have performed their basic duties and functions fairly well. It's seen from the division of work that's not just accumulated in one of the officers. Lurah as head of office and secretary lurah as chief of office has done his job while monitoring and overseeing his employees. In terms of timing, it appears that the Lurah Sei White Office has already tried to complete the letter on time but there are still frequent delays because Lurah is often not in the office and can not sign the letter. In the case of typing also Lurah Sei White Central Office still frequently occur typing errors caused by the number of files that come in with the same deadline so that the lack of concentration resulted in typing mistakes to writing errors on the file. Kantor Lurah Sei Putih Tengah has performed its administrative tasks quite well but not to the maximum.